Ensaio e simulação computacional de estrutura geodésica tipo icosaedro truncado construída com barras de bambu - Castro, Gustavo Correa de (2019)
Geodesic structures are important because they are light, stable and can overcome large free gaps between their structure. This is due to the shape of the dome, which allows a homogeneous distribution throughout the structure. This feature allows for lower consumption of raw material, which reduces costs both economically and natural resources. One of the problems encountered when constructing geodesic structures is the connection between structural profiles. The search for natural resources allows new materials to be used in engineering, bamboo fits in this context. The bamboo culm is a vegetable tube that has good mechanical and physical properties that allow its use as a structural material. An important characteristic of bamboo culm is that it has low specific mass (density). In this study, we analyzed different materials for union and their respective behaviors. Test specimens were prepared and then bending tests were performed. It has been concluded that the best solution is the use of blades tied to the joints between the bamboo bars. The solution is positive by: allowing roofing to be used, reducing the use of industrial materials, reducing visual impacts due to the combination of materials and conserving the properties of the geodetic structure and bamboo bars used. From these initial conclusions, a mold was built and then two models of truncated icosahedron type geodesic structure composed of hexagons and pentagons composed of bamboo bars. The edges of these geometries are the same, so the segments of bamboo bars are all the same length. Vertical loading tests were applied to the two models, based on the results obtained in the loads, it can be concluded: which unions suffer most with loading effects and as loading occurs, the structure is arranged and from a certain moment the variation of vertical displacement is considerably reduced. Evaluating the structure by the finite element method using the ANSYS program, one can analyze the unions that suffer the most with loading application. Evidencing that the experimental data are compatible with the computational simulation. In this way, to optimize the structure the ideal is to apply reinforcement in these unions. The results obtained help to conclude that simple tests, such as vertical loading, can extract data from reality without major investments, and the computational simulation helps to better understand the evaluated behavior.